The Impact of Artificial Intelligence on the Banking Industry and How AI is altering the Characteristics of Modern Banks (International Journal of Food and Nutritional Sciences, 2022)
Artificial intelligence (AI) is revolutionizing conventional banking techniques and consumer reports within the banking enterprise. This paper investigates AI's multifarious impact on present-day banks, clarifying its huge range of uses and vital function in redefining banking attributes. Banking industry has seen a change in client engagement paradigm also operational efficiency with the introduction of AI-powered technologies like chatbots, mobile banking, and block chain. Chatbots, including the SBI Intelligent Assistant, are reworking consumer care with personalized interactions that mimic those of human customer service experts. In a comparable vein, AI-driven apps are redefining cellular banking experiences, allowing frictionless transactions and customized monetary statistics. Furthermore, block chain generation shows promise now not simply as the muse of cryptocurrencies but also as a strong way to improve record integrity and transaction protection in economic systems. By integrating AI algorithms, fraud detection structures are fueled, taking into account proactive chance mitigation methods and real-time sample identity. The look at gives empirical findings that constitute purchaser reviews on AI applications in banking and are based on survey information and statistical evaluation. Positive correlations between perceived AI blessings, such as progressed safety and monetary recommendation, are proven by correlation evaluation, which will increase the probability that customers will embrace AI-driven offerings. Additionally, in comparison to other age businesses, a chi-square analysis revealed a vast tendency among younger respondents to acknowledge the general advantages of AI in banking. This observe predicts a dynamic destiny for the banking industry by highlighting the changing banking environment pushed with the aid of AI advancements and shedding light on the jointly beneficial hyperlink between AI technology and purchaser choices.